Exploring the relationship between chronic pain and mental health disorders: a case-control study at a tertiary care hospital - Payal Godria; Meet Ghonia; Dia Verma; Nilay Shetal Patel; Rudra Shetal Patel; Kushal Kiritkumar Salunke; Divyang S. Bhudhrani (International Journal of Research in Medical Sciences, 2026)
Background: Chronic pain is a multifaceted condition that significantly affects patients’ quality of life and has been closely associated with mental health disorders such as depression, anxiety, and stress-related conditions. This study aimed to explore the association between chronic pain and mental health disorders among patients at a tertiary care hospital in India. Methods: We conducted a case-control study involving 200 participants at a tertiary care hospital, from January 2024 to June 2024. The case group consisted of 100 patients diagnosed with chronic pain for more than three months, while the control group included 100 matched individuals without chronic pain. Data on depression, anxiety, and stress were collected using the validated depression, anxiety and stress scale-21 (DASS-21). Dietary and lifestyle habits, sleep quality, and socioeconomic factors were assessed through structured questionnaires. Statistical analysis was conducted using multivariate logistic regression to adjust for confounding variables, including age, gender, socioeconomic status, and comorbidities. Results: The prevalence of symptoms of depression, anxiety, and stress in the chronic pain group was significantly higher compared to controls. The adjusted odds ratio (OR) for depression among the chronic pain group was 3.82 (95% CI: 2.05-7.13, p